Implementasi Aplikasi “SahabatAnabul” Berbasis User Centered Design Sebagai Website Pangkalan Informasi Anabul - Ni Luh Putu Ayu Siwastuti Cayadewi; Made Agung Raharja (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Currently, many people keep animals in their homes. Most of the animals they have are dogs and cats. Thus, they need a lot of information about the animals they keep. Therefore, to make it easier for people to find information about Anabul, an information website about Anabul was created, starting from the types of Anabul, its characteristics, what Anabul needs, and others. This journal produces a website based SahabatAnabul application. SahabatAnabul is a website to share all information about anabul, especially for dogs and cats. The resulting website can help people who have pets or want to know information about the types of dogs and cat breeds that exist in the world.